2000
DOI: 10.1111/1467-9507.00109
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and Social Functioning: A Longitudinal Study from Infancy to Middle Childhood

Abstract: A longitudinal sample of 96 children was followed from 15 months of age to 8-9 years. Attachment relationships were studied in infancy with the Strange Situation and at school age with the Separation Anxiety Test. Social functioning was studied at school age through mother and teacher ratings, observations at school, and in children's selfreports. Predictive results showed that infants who had been secure as infants were more socially active, positive and popular at school age, and tended to report less social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
139
2
14

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(163 citation statements)
references
References 21 publications
8
139
2
14
Order By: Relevance
“…Contrary to some previously reported results (e.g., Bohlin et al, 2000) differences between ambivalence and avoidance were found. Interestingly, children who reported higher levels of avoidance at Time 2 also reported less social anxiety in new situations, indicating that avoidance may serve an adaptive function in some contexts.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to some previously reported results (e.g., Bohlin et al, 2000) differences between ambivalence and avoidance were found. Interestingly, children who reported higher levels of avoidance at Time 2 also reported less social anxiety in new situations, indicating that avoidance may serve an adaptive function in some contexts.…”
Section: Discussioncontrasting
confidence: 99%
“…Three studies have tested whether attachment is specifically related to social anxiety. In a longitudinal study, Bohlin Hagekull, and Rydell, (2000) assessed attachment security in infancy and at age 9, and evaluated social anxiety at age 9. Children who had been secure as infants or at age 9 reported less social anxiety than children who had been insecurely attached.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand and interpret this brand new world and environment, the child is entirely dependent on the parent's facial expressions, their tone of voice and their body language [7]. A close physical proximity has two functions and this is to protect the child from danger and to begin to teach the child what it means to exist in a social world [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This need is indicated by researchers who have shown a relationship between insecure attachment in children who are typically developing and behavior problems in preschool, adolescence, and adulthood (e.g., Bohlin, Hagekull, & Rydell, 2000;Park & Waters, 1989). These studies highlight the need for early identification and treatment of children who may (without treatment) later engage in criminal or harmful acts toward people and institutions in our society.…”
Section: Introductionmentioning
confidence: 99%